Psichiatria e psicoterapia a Cuba. Un dialogo con Alexis Lorenzo Ruiz - Carlotto, Alessandra (Il sogno della farfalla, 2023)
Psychiatry and psychotherapy in Cuba. A dialogue with Alexis Lorenzo Ruiz In this issue, we propose an interview to the President of the Cuban Society of psychology and receiver of the 2017 Apa Presidential Citation award, Alexis Lorenzo Ruiz. His testimony allows to identify the most crucial pillars of Cuban mental health system, including equal access to care, holistic approach in treatment and a psycho-social approach to patient. The interviewed places a particular emphasis on the therapeutic treatments adopted, in particular the psychotherapeutic approach, and on the specific attention on programs such as prevention, health promotion and early intervention.